New taxa and new records of butterflies from Vietnam (Lepidoptera, Papilionoidea) - Monastyrskii, Alexander L.; van Lien, Vu (Zootaxa, 2021)
A new species and eight new subspecies of Papilionoidea discovered in Vietnam between 2002 and 2020 are described and illustrated. The status of two taxa are revised. New taxa include Pieridae: Delias sanaca bidoupa Monastyrskii & Vu subspec. nov. and Talbotia naganum aurelia Monastyrskii & Vu subspec. nov.; Nymphalidae: Abrota ganga pulcheria Monastyrskii & Vu, subspec. nov.; Bassarona recta consonensis Monastyrskii & Vu, subspec. nov.; Pantoporia bieti aurantina Monastyrskii & To subspec. nov.; Ragadia latifasciata cristata Monastyrskii & Vu, subspec. nov.; Ragadia latifasciata crystallina Monastyrskii & Vu, subspec. nov.; Faunis indistincta luctus Monastyrskii & Vu subspec. nov. & Aemona gialaica Monastyrskii, K. Saito & Vu, spec. nov. The taxon infuscata Devyatkin & Monastyrskii, previously described as the subspecies Aemona tonkinensis infuscata, was elevated to the species level, while the taxon critias (Ragadia critias Riley & Godfrey) was reduced to a subspecies. Three Satyrinae species were recorded from Vietnam for the first time: Palaeonympha opalina Butler, 1871; Ypthima motschulskyi Bremer & Grey, 1853; and Ragadia latifasciata Leech, 1891.